2019
DOI: 10.1002/anie.201902677
|View full text |Cite
|
Sign up to set email alerts
|

A Self‐Assembled Bicontinuous Cubic Phase with a Single‐Diamond Network

Abstract: The first single-diamond cubic phase in al iquid crystal is reported. This skeletal structure with the Fd " 3mspace group is formed by self-assembly of bolaamphiphiles with swallow-tailed lateral chains.I tc onsists of bundles of pconjugated p-terphenyl rods fused into an infinite network by hydrogen-bonded spheres at tetrahedral four-way junctions. We also present aq uantitative model relating molecular architecture to the space-filling requirements of six possible bicontinuous cubic phases,t hat is,t he sing… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
45
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 34 publications
1
45
0
Order By: Relevance
“…π* transition of non-bonded electrons of imine (C=N) groups or π-tovacant B p-orbital transition was observed in the range 357-527 nm in C 2 H 5 OH or CHCl 3 , respectively. [47] The NMR ( 1 H, 13 C, and 11 B) spectral data were in good agreement with the proposed structures in CDCl 3 or DMSO-d 6 ( Figure S1-S16 in the ESI). The major difference between the 1 H NMR spectra of ligands (T 1 and T 2 ) and their complexes (T (1-2) B (1-2) ) and (T (1-2) B (1-2) -N) is the presence of a new signal for the boronic acid groups and 4-tert-butyl pyridine ( Figure S1-S10 in the ESI).…”
Section: Spectroscopic Studiessupporting
confidence: 77%
See 1 more Smart Citation
“…π* transition of non-bonded electrons of imine (C=N) groups or π-tovacant B p-orbital transition was observed in the range 357-527 nm in C 2 H 5 OH or CHCl 3 , respectively. [47] The NMR ( 1 H, 13 C, and 11 B) spectral data were in good agreement with the proposed structures in CDCl 3 or DMSO-d 6 ( Figure S1-S16 in the ESI). The major difference between the 1 H NMR spectra of ligands (T 1 and T 2 ) and their complexes (T (1-2) B (1-2) ) and (T (1-2) B (1-2) -N) is the presence of a new signal for the boronic acid groups and 4-tert-butyl pyridine ( Figure S1-S10 in the ESI).…”
Section: Spectroscopic Studiessupporting
confidence: 77%
“…π* transition of non-bonded electrons or π-to-vacant B p-orbital transitions. [47] In view of the this results, the strong broad absorption bands in the range 218-346 nm in C 2 H 5 OH or CHCl 3 , respectively, can be attributed to the π ! π* transitions of aromatic benzene ring.…”
Section: Spectroscopic Studiesmentioning
confidence: 72%
“…[20] Fors uch "normal" wedges it has been shown that ak ey determinant of the adopted phase type is the dV/dr function, describing how volume increases as one moves along r from the apex (r = 0) toward the wide end of the wedge. [21] The same principle can be applied to the present inverse wedges. As af irst approximation, the cross-section area A of the wedge is A(r) / dV/dr / r q .H ere q % 1( slice or triangle shape) suites ac olumnar phase (Figure 4a), q % 0( rectangle, matching aromatic and aliphatic cross-sections) suits alamellar phase (Figure 4c), while 0 < q < 1( shield shape) is most likely to adopt aCub bi phase (Figure 4b).…”
Section: Angewandte Chemiementioning
confidence: 88%
“…The method of selecting the correct phase combination is described in previous work. 12 , 25 , 27 The cubic lattice parameter is around 11–13 nm for Ia 3[combining macron] d and 18 nm for I 23 [ * ] , in line with a double- and triple-network structure, respectively. Remarkably, the Ia 3[combining macron] d lattice is the largest for the smallest molecule 3/2 ( L mol = 4.4 nm; a cub = 12.9 nm) and becomes smaller for the Ia 3[combining macron] d phases of the larger compounds 3/12–3/16 with much longer chains ( L mol = 5.8–6.3 nm; a cub = 11.3–11.5 nm).…”
mentioning
confidence: 94%